Optimization of Transformative Leadership to Enhance Organizational Performance: Policing Strategic Analysis at Industrial Revolution 4.0 Era to Maintain Security and Public Order - Latif, Muh. Wahyudin; Dwilaksana, Chryshnanda; Nasri, Nasri; Wardana, Gusde (Faculty of Law, Universitas Airlangga, 2024)
Abstract The Bojonegoro Resort Police, a middle manager in the Indonesian National Police, proactively adapts to the Fourth Industrial Revolution's challenges, marked by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity). They prioritize staying informed about developments and taking initiative. Strategies for security and public order maintenance, including crime prevention and increased surveillance, are effectively planned and implemented. Qualitative field research explores how transformative leadership optimizes policing and performance. Findings reveal: 1) Leaders model idealized influence and inspire a shared vision; 2) They provide inspirational motivation; 3) Leaders foster intellectual stimulation by promoting skill development and critical thinking; 4) Individualized consideration is shown through active delegation and control measures. In conclusion, the Bojonegoro Resort Police's proactive, transformative leadership helps them navigate the Fourth Industrial Revolution's challenges, enhancing organizational performance in maintaining security and public order.